2023
DOI: 10.3390/v15081701
|View full text |Cite
|
Sign up to set email alerts
|

A Temperate Sinorhizobium Phage, AP-16-3, Closely Related to Phage 16-3: Mosaic Genome and Prophage Analysis

Abstract: Soil Sinorhizobium phage AP-16-3, a strain phylogenetically close to Rhizobium phage 16-3, was isolated in a mountainous region of Dagestan, belonging to the origin of cultivated plants in the Caucasus, according to Vavilov N.I. The genome of phage AP-16-3 is 61 kbp in size and contains 62 ORFs, of which 42 ORFs have homologues in the genome of Rhizobium phage 16-3, which was studied in the 1960s–1980s. A search for Rhizobium phage 16-3-related sequences was performed in the genomes of modern strains of root n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…However, when searching for the R-M system in the host genome using rmsFinder, none R-M system was detected (Roberts et al, 2015), leading us to reconsider the reasoning behind the presence of methyltransferases in vB_LagS-V1. Recent analysis revealed that temperate phages are more prone to encoding methyltransferases compared to virulent phages (Kozlova et al, 2023), consistent with the observed prevalence of methyltransferases in the temperate phage, vB_LagS-V1. The over-representation of methyltransferases in temperate phages implies that methyltransferases more likely help the temperate phage to sustain the lysogenic state, and potentially provide protection to the host against infection by other phages (Oliveira et al, 2014;Kozlova et al, 2023).…”
Section: Dna Methyltransferasessupporting
confidence: 68%
See 1 more Smart Citation
“…However, when searching for the R-M system in the host genome using rmsFinder, none R-M system was detected (Roberts et al, 2015), leading us to reconsider the reasoning behind the presence of methyltransferases in vB_LagS-V1. Recent analysis revealed that temperate phages are more prone to encoding methyltransferases compared to virulent phages (Kozlova et al, 2023), consistent with the observed prevalence of methyltransferases in the temperate phage, vB_LagS-V1. The over-representation of methyltransferases in temperate phages implies that methyltransferases more likely help the temperate phage to sustain the lysogenic state, and potentially provide protection to the host against infection by other phages (Oliveira et al, 2014;Kozlova et al, 2023).…”
Section: Dna Methyltransferasessupporting
confidence: 68%
“…The hosts of these three phages belong to the Labrenzia and have been isolated from marine environments. Whereas, other members such as Rhizobium phage RHph_TM3_3_14B, Rhizobium phage RHph_Y3_1, Sinorhizobium phage AP-16-3 and Rhizobium phage 16-3 originate from rhizobia isolated from soil environments (Ordogh and Szende, 1961;Santamarıá et al, 2022;Kozlova et al, 2023). This divergence in host and corresponding environments highlights a significant ecological distinction of vB_LagS-V1 and its associated new genus.…”
Section: Vb_lags-v1 Represents a New Genusmentioning
confidence: 99%